Multi-Modal User Interactions in Controlled Environments - Djeraba, Chaabane; Lablack, Adel.; Benabbas, Yassine; SpringerLink (Online service) (Boston, MA : Springer US, 2010)
Multi-Modal User Interactions in Controlled Environments investigates the capture and analysis of user$1 (Bs multimodal behavior (mainly eye gaze, eye fixation, eye blink and body movements) within a real controlled environment (controlled-supermarket, personal environment) in order to adapt the response of the computer/environment to the user. Such data is captured using non-intrusive sensors (for example, cameras in the stands of a supermarket) installed in the environment. This multi-modal video based behavioral data will be analyzed to infer user intentions while assisting users in their day-to-day tasks by adapting the system$1 (Bs response to their requirements seamlessly. This book also focuses on the presentation of information to the user. Multi-Modal User Interactions in Controlled Environments is designed for professionals in industry, including professionals in the domains of security and interactive web television. This book is also suitable for graduate-level students in computer science and electrical engineering.s
Abnormal Event Detection -- Flow Estimation -- Estimation of Visual Gaze -- Visual Field Projection and Region of Interest Analysis -- Conclusion.
Keywords: Computer science; Information storage and retrieval systems; Multimedia systems; Artificial intelligence; Computer vision; Biometrics; Computer Science; Multimedia Information Systems; User Interfaces and Human Computer Interaction; Artificial Intelligence (incl. Robotics).; Biometrics; Computer Imaging, Vision, Pattern Recognition and Graphics; Information Storage and Retrieval